Shifting regional dynamics urgently require better US strategic communications and Southeast Asia policy adaptation - Mitchell, Derek (2024)
Regional dynamics are shifting despite the best efforts of the US and Southeast Asia to maintain a stable status quo. To protect their interests, this Commentary recommends that the US up its strategic communications game and Southeast Asia raise its voice more assertively to shape governance norms in the 21st century.